Following Trump: Are Evangelicals Willing Participants in a "New" Religion? - Myers, William R. (Theology today, 2019)
This article traces how premillennial theology replaced postmillennialism and prepared the way for evangelical identification with Trump's negative worldview. It suggests, following The Altars Where We Worship, multiple ways postmodern humans meet basic human impulses. It details how such "altars" end up serving in markedly religious ways. Using Ninian Smart's seven categories, it suggests how Trump and those who follow him fit what might be a "new" religion. Finally, the article relates how Moltmann's understanding of resurrection gives Christians a place to stand in this Trumpian era.